Kontekstualisasi Pemahaman Hadîth dan Rekonstruksi Epistemologi Ikhtilâf dalam Fiqh al-Hadîth - Amin, Muhammadiyah (ISLAMICA: Jurnal Studi Keislaman, 2011)
Hadith, a prophetic saying has been a living tradition for the Muslims. In their plea to live a better live, Muslims would turn to either the Qurâan or the hadith. It has in other words served as a source for all aspects of the lives of Muslims. As an object of academic study, hadith has also been subjected into a serious investigation both to prove its authenticity in its narration and message, and to elaborate certain points of importance. Critical studies of hadith have been common in academic circles in the Muslim world and in the Western universities, one of which focuses on the contextual meaning of it. It is toward this end that this paper is aimed at. It is an attempt to make a contribution in the contextual analysis of hadith. By contextual analysis we mean a study that puts a lot of stressing on the meaning of a hadith by looking at the context from which it was said or reported. This way of studying hadith would help to understand it better in line with the dynamic nature of Islam. The paper argues that a hadith cannot be understood in isolation from its context. It also maintains that understanding its context would mean that one would be able to unveil and even reconstruct the hadith epistemology. Since the epistemology of a hadith lies in its meaning, the re-interpretation of a hadith according to its context would mean rediscovering the new dimension of the epistemology.